Sikap perilaku, norma subjektif , kendali perilaku persepsian terhadap intensi manajer dalam kecurangan di moderasi locus of control - Nikmatuniayah, Nikmatuniayah; Yudhaningsih, Resi; Mardiana A, Lilis; Hartono, Hartono (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of Behavioral Attitudes, Subjective Norms, Perceived Behavioral Controls on managers' intentions in committing fraudulent financial statement presentations. Specifically, this study aims to investigate the effect of managers' attitudes, subjective norms, perceived behavioral control on managers' intentions in committing fraudulent financial statement presentations, moderated by locus of control within Banks in Indonesia. This study uses quantitative methods. The subjects of this research are managers or heads of sections who work at Bank Bank Indonesia. Respondent samples were taken from 50 conventional and Islamic banks in the city of Semarang. The results showed that there was an influence of attitude towards behavior, perceived behavioral control, on managers' intentions in fraudulent financial statement presentations. On the other hand, the subjective norm variable has no effect on managers' intentions in fraudulent financial statement presentations. Based on the results of data processing, it was found that there was no influence of the locus of control variable on the manager's intention in fraudulent financial statement presentation. Overall, it was found that locus of control moderated the influence of behavioral attitudes, subjective norms, and perceived behavioral control on managers' intentions in fraudulent financial statement presentations.